Influence Country of Origin, Brand Image, Product Quality, and Price on Purchasing Decisions of Wardah Cosmetic Products (Consumer Study at Valette shop Cosmetic Store) - Rahmawati, Husnul; Yunarni, Baiq Reinalda Tri; Hadi, Sulhan; Ramayanto, Ramayanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study examines the influence of Country Of Origin, Brand Image, Product Quality, and Price on Consumers Purchase Decisions of Wardah Cosmetic Products at Valette shop Cosmetic Stores. This type of research is quantitative with a sample size of 100 respondents. The data analysis method used is multiple linear regression which aims to determine how much influence each independent variable has on purchasing decisions. The results of the study indicate that: 1) Country Of Origin has a significant effect on Purchase Decisions of Wardah Cosmetic Products. 2) Brand Image has a significant effect on Purchase Decisions of Wardah Cosmetic Products. 3) Product Quality has a significant effect on Purchase Decisions of Wardah Cosmetic Products. 4) Price has a significant effect on Purchase Decisions of Wardah Cosmetic Products.